Silence of the Innocents: Illegal Immigrants' Underreporting of Crime and their Victimization - Stefano Comino; Giovanni Mastrobuoni; Antonio Nicolò (Institute for the Study of Labor (IZA), 2016)
We analyze the consequences of illegally residing in a country on the likelihood of reporting a crime to the police and, as a consequence, on the likelihood to become victims of a crime. We use an immigration amnesty to address two issues when dealing with the legal status of immigrants: it is both endogenous as well as mostly unobserved in surveys. Right after the 1986 US Immigration Reform and Control Act, which disproportionately legalized individuals of Hispanic origin, crime victims of Hispanic origin in cities with a large proportion of illegal Hispanics become considerably more likely to report a crime. Non-Hispanics show no changes. Difference-in-differences estimates that adjust for the misclassification of legal status imply that the reporting rate of undocumented immigrants is close to 11 percent. Gaining legal status the reporting rate triples, approaching the reporting rate of non-Hispanics. We also find some evidence that following the amnesty Hispanics living in metropolitan areas with a large share of illegal migrants experience a reduction in victimization. This is coherent with a simple behavioral model of crime that guides our empirical strategies, where amnesties increase the reporting rate of legalized immigrants, which, in turn, modify the victimization of natives and migrants.
Keywords: J15; K37; K42; R23; 330; immigration; amnesty; crime reporting; victimization survey